THE STUDY ON IN VITRO DIGESTIBILITY OF SOAKED PALM OIL FIBER BY FILTRATED PALM OIL FRUIT BUNCH ASH - Darmawan, Ari L.; IRAWAN, ASEP; DHALIKA, TIDI; TARMIDI, ANA R.; -, MANSYUR; BUDIMAN, ATUN; KAMIL, KURNIA A.; HERNAMAN, IMAN (Majalah Ilmiah Peternakan; Vol 17 No 1 (2014): Vol 17, No 1 (2014), 2014)
Palm oil fiber has its potency as feed fiber source for ruminant, but contains high lignin and causes limited digestibility. This research was carried out to find the effect of soaking palm oil fiber in filtrated palm oil fruit bunch ash (FPOFBA) on in vitro digestibility. This experiment used a completely randomized design that repeated for 4times. Palm oil fruit bunch ash was mixed in water and entered into container for 24 hours within concentrations, consists of: 50, 100, 150 and 200 g/L. Moreover, this filtrate used to soak palm oil fiber for 3 hours. The processed products were analyzed for their level of lignin and crude fiber. Meanwhile, in vitro test was used to measure digestibility. It showed that soaking in filtrated palm oil fruit bunch ash gave significant effect to decrease level of lignin and crude fiber (P<0.05), and without soaking to improve digestibility of dry and organic matter compared to control treatment (P<0.05). Treatment with 150 g/L and 200 g/L using filtrated palm oil fruit bunch ash produced low level of lignin (P<0.05), as of: 17.25 and 18.53%. In contrast, within concentration of 150 g/L produced higher level of crude fiber compared to 200 g/L (46.04 vs. 43.87%). This seemed to have the same results in digestibility of dry and organic matter (P>0.05), such as 23.48 and 24.12% as well as 16.70 and 17.06 % in each. It can be concluded that soaked palm oil fiber with 150 g/L concentration of filtrated palm oil fruit bunch ash was more effective in improving digestibility.
Keywords: ash, crude fiber, digestibility, lignin, and palm oil